Sergey Fedoroff: A Pioneer of the Neuronal Regeneration. Tribute from the Pan American Association of Anatomy - Losardo,Ricardo Jorge (Sociedad Chilena de Anatomía, 2015)
Sergey Fedoroff (1925-2012) is considered the father of tissue culture because of his important findings and contributions. He was president of several societies, such as the Pan American Association of Anatomy.